Dependence or Self-Reliance?: The Philippine NGO Experience - Mendoza, Diana J (Archīum Ateneo, 2012)
The sociopolitical significance of nongovernmental organizations (NGOs) in the developing countries has received considerable attention from academic and development circles and among donors. When the top-down "blueprint" approach of the public sector fell into ill-repute, funding increased for NGOs beginning in the late 1960s. The debt crisis of the 1980s and the dramatic increase in poverty which followed from its wake triggered international response on a massive scale. International NGOs expanded their levels of operations to cover more countries.